The Effects of Literature-Based Learning Experience Provision to Promote Body Protection from Sexual Abuse of Young Children - Senagoon, Walailuck; Lehmongkol, Pattamavadi (Interdisciplinary Academic and Research Journal, 2023)
Organizing experiences using literature for early childhood children is an experience that uses fairy tales to help children enjoy, enjoy, understand the role of the characters, and can learn whether the character's actions are good or bad, and how they can be used in everyday life. The literature helps children understand easily because they use language that is easy for children to understand and can be read aloud to teachers or friends. Thus, this study aimed to study the effects of literature–based learning experience provision to promote body protection from sexual abuse of young children. The target group was 15 male and female children aged between 4 - 5 years old, studying in kindergarten level 2, semester 2, the academic year 2022, Ramkhamhaeng University Demonstration School (Elementary Department). Tools used in the study were 24 lesson plans on literature-based learning experiences for young children and an assessment form on sexual abuse body protection capability for young children. Data were analyzed using mean and standard deviation. Qualitative data were analyzed by content analysis. The results found that young children who participated in the literature–based learning experience provision had a mean score of 10.20 which was higher than before participated. Therefore, the literature–based learning experience provision contributed to body protection from sexual abuse of young children.